Phylodynamic analysis and spike protein mutations in porcine deltacoronavirus with a new variant introduction in Taiwan. Issue 2 (24th November 2021) - Hsueh, Fu-Chun; Wu, Cheng-Nan; Lin, Marco Yung-Cheng; Hsu, Feng-Yang; Lin, Chuen-Fu; Chang, Hui-Wen; Lin, Jih-Hui; Liu, Hsin-Fu; Chiou, Ming-Tang; Chan, Kuan Rong; Lin, Chao-Nan
Abstract: Porcine deltacoronavirus (PDCoV) is a highly transmissible intestinal pathogen that causes mild to severe clinical symptoms, such as anorexia, vomiting, and watery diarrhea in pigs. By comparing the genetic sequences of the spike glycoprotein between historical and current Taiwanese PDCoV strains, we identified a novel PDCoV variant that displaced the PDCoV responsible for the 2015 epidemic. This PDCoV variant belongs to a young population within the US lineage, and infected pigs carry high concentrations of the virus. It also has several critical point mutations and an amino acid insertion at position 52 that may enhance the affinity between the B-cell epitopes located in the N-terminal domain with its complementarity regions, consequently facilitating binding or penetration between the fusion peptide and cellular membrane. Furthermore, viral protein structure prediction demonstrated that these amino acid changes may change the ability of the virus to bind to the receptor, which may consequently alter virus infectivity. Our results hence suggest the emergence of new PDCoV strains in Taiwan with the potential for greater transmission and pathogenesis.